2008
DOI: 10.1097/mao.0b013e31815dbafc
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Results With Intratympanic Dexamethasone in the Treatment of Ménière's Disease

Abstract: Objective-To assess patient satisfaction with vertigo control using intratympanic (IT) dexamethasone (12 mg/mL) for medically refractory unilateral Ménière's disease.Study Design-Retrospective study. Setting-Tertiary referral neurotology clinic.Patients-One hundred twenty-nine subjects diagnosed with unilateral Ménière's disease still having vertigo despite medical therapy. Intervention-IT dexamethasone injections as needed to control vertigo attacks.Main Outcome Measure-A Kaplan-Meier time-to-event method was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(65 citation statements)
references
References 21 publications
3
62
0
Order By: Relevance
“…Three papers did not specify their diagnostic criteria for MD [13,19,22]. For follow-up length, the more recent papers ensured 2 years of follow-up [10,14,15,20]. The other papers ranged in follow-ups from as short as 1 month [19] to up to 20 months [16].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three papers did not specify their diagnostic criteria for MD [13,19,22]. For follow-up length, the more recent papers ensured 2 years of follow-up [10,14,15,20]. The other papers ranged in follow-ups from as short as 1 month [19] to up to 20 months [16].…”
Section: Resultsmentioning
confidence: 99%
“…A negative study is one that concluded that steroids were not beneficial, but not harmful either, for the treatment of MD. Among the 13 MD studies, 8 were positive [10,12,13,14,18,20,21,22] and 5 were negative [11,15,16,17,19]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing the treatment group (dexamethasone) with the placebo group after 24 months demonstrated a statistically significant improvement in vertigo as defined by a respective improvement in the class (82% versus 57% of patients achieving class A -complete con-trol) and a mean vertigo subjective improvement (90% versus 57%). Boleas-Aguirre [5] published a study in 2008 of 129 patients with MD receiving intratympanic treatment with 12 mg/mL of dexamethasone. Satisfactory vertigo control (meaning no further treatments were needed or asked for) was achieved in 117 (91%) of 129 cases.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, 91% had control of dizziness with intratympanic dexamethasone, and some needed more injections of dexamethasone or associated intratympanic gentamicin [22].…”
Section: Intratympanic Corticosteroid and Meniere's Symptomsmentioning
confidence: 99%